Lipid raft disruption inhibits the activation of Transient Receptor Potential Vanilloid 1, but not TRP Melastatin 3 and the voltage-gated L-type calcium channels in sensory neurons - Payrits, Maja; Zsidó, Balázs Zoltán; Nehr-Majoros, Andrea Kinga; Börzsei, Rita; Helyes, Zsuzsanna; Hetényi, Csaba; Szőke, Éva (Frontiers in Cell and Developmental Biology, 2024)
Transient Receptor Potential (TRP) ion channels like Vanilloid 1 (TRPV1) and Melastatin 3 (TRPM3) are nonselective cation channels expressed in primary sensory neurons and peripheral nerve endings, which are located in cholesterol- and sphingolipid-rich membrane lipid raft regions and have important roles in pain processing. Besides TRP ion channels a wide variety of voltage-gated ion channels were also described in the membrane raft regions of neuronal cells. Here we investigated the effects of lipid raft disruption by methyl-beta-cyclodextrin (MCD) and sphingomyelinase (SMase) on TRPV1, TRPM3 and voltage-gated L-type Ca2+ channel activation in cultured trigeminal neurons and sensory nerve terminals of the trachea. We also examined the mechanism of action of MCD by in silico modeling. Disruption of lipid rafts by MCD or SMase did not alter CIM0216-induced TRPM3 cation channel activation and the voltage-gated L-type Ca2+ channel activation by FPL 64126 or veratridine neither on trigeminal sensory neurons nor sensory nerve terminals. We provided the first structural explanation with in silico modeling that the activation of TRPV1, TRPM3 and voltage-gated L-type Ca2+ channels is affected differently by the cholesterol content surrounding them in the plasma membrane. It is concluded that modifying the hydrophobic interactions between lipid rafts and ion channels might provide a selective novel mechanism for peripheral analgesia.